Pengembangan Produk Kasippi Berbasis Pangan Lokal Loka Pere Khas Mandar Sebagai Alternatif Cemilan Penderita Hipertensi - Syah, Justiyulfah; Abdullah, Anisa Dwirizky; Ningsi, Nurpatwa Wilda (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to develop a kasippi product based on local food loka pere‘ typical of Mandar as an alternative snack for hypertension sufferers through physical and organoleptic tests. This study was conducted using a one-factor Randomized Block Design method with 5 treatments. Acceptability was measured from the level of preference including color, aroma, taste and texture of hardness and crispness using a hedonic scale. Data analysis was carried out using a diversity test and Duncan’s advanced test. The results of the organoleptic test by the panelists showed that the most preferred Formula was Formula 2, namely with the addition of 30% lokapere flour, with the results of the P2 color assessment that the panelists preferred most was pale brown, the most preferred F2 aroma was slightly banana-scented, the most preferred F2 taste was sweet and quite banana-like, and the most preferred F2 texture was based on crispness and hardness. The study showed that the addition of loka pere flour to kasippi had a significant effect on the organoleptic test including the level of preference and hedonic quality of kasippi.